Accountability and social responsibility international perspectives - Crowther, David; Lauesen, Linne Marie (Bingley, U.K. : Emerald, 2016)
Probably since the mid-1980s, corporate governance has attracted a great deal of attention from corporate managers and investors protection has become a much more important issue for all financial markets after recent firm failures and scandals. Especially important for all with an interest in how organizational governance is formed around socially responsible and accountable ways of leadership and management, this book provides new insights into various issues regarding business management and governance, and points to ways for businesses to make a real change for the betterment of the world, especially in the aftermath of the recent financial crisis 2007/2008.
Organisational governance and strategic csr to strengthen local supply chains navigating the maze / Veronica Broomes -- The governance of sustainable development / David Crowther, Shahla Seifi -- The role of the (governance of the) arts in cultural sustainability: a case study of music / Linne Lauesen -- Organisational governance and accountability: do we have anything to learn from studying african traditional societies? / Miriam Green -- Microfinance performance in financial markets: the case of microfinance investment vehicles / Erwan Le Saout, La<U+0302>ma Daher -- CSR practices in leading Indian banks / Abhishek Gon, Cristina Mititelu -- Reorganisation problems of the auditing firms in the post Sarbanes Oxley era: quality concern and Turkey / Iffet Kesimli -- Stakeholder dissonance: corporate social responsibility versus regulation - a study of a trust-recovery process / Linne Lauesen -- 140 Characters for CSR communication: an exploration of twitter engagement of Fortune companies / Lina Gomez, Lucely Vargas-Preciado -- Corporate social responsibility patterns of small and medium enterprises (SMEs) industries consumers: how to improve the situation in sub-saharan Africa / Nini Sulamoyo.
Includes bibliographical references.
Print version record
Keywords: Business ethics; Business & management; Social responsibility of business